Practice Level and Associated Factors Towards the Preventive Measures of COVID-19 Among the General Population; A Systematic Review and Meta-Analysis - Abay Woday Tadesse; Abay Woday Tadesse; Abay Woday Tadesse; Setognal Birara Aychiluhm; Kusse Urmale Mare; Setegn Mihret Tarekegn; Setegn Mihret Tarekegn; Gebeyaw Biset; Gebeyaw Biset (Frontiers Media S.A., 2022)
BackgroundStudies conducted on the practice of COVID-19 preventive methods across the world are highly inconsistent and inconclusive. Hence, this study intended to estimate the pooled preventive practice and its determinants among the general population.MethodsThis study was conducted using online databases (PubMed, HINARI, Scopus, EMBASE, Science Direct, and Cochrane library database), African Journals online, Google Scholar, open gray and online repository accessed studies. The quality of the included studies was assessed using Newcastle-Ottawa Quality Assessment Scale (NOS). STATA 14.0 software for analysis. The existence of heterogeneity between studies was checked using Cochran Q test and I2 test statistics and then, the presence of publication bias was detected using both funnel plot and Egger's test.Results51 studies were included and the pooled level of practice toward the preventive measures of COVID-19 was 74.4% (95% CI: 70.2-78.6%, I2 = 99.7%, P < 0.001] using a random effects model. Being female [OR = 1.97: 95% CI 1.75, 2.23; I2 = 0.0%, P < 0.698], rural residence [OR = 0.53: 95% CI 0.44, 0.65; I2 = 73.5%, P < 0.013], attending higher education level [OR = 1.47: 95% CI 1.18, 1.83; I2 = 75.4%, P < 0.001], being employed [OR = 2.12: 95% CI 1.44, 3.12; I2 = 91.8%, P < 0.001], age < 30 [OR = 0.73: 95% CI 0.60, 0.89; I2 = 73.9%, P < 0.001], and knowledgeable [OR = 1.22: 95% CI 1.09, 1.36; I2 = 47.3%, P < 0.077] were the independent predictors of adequate practice level.Conclusionsnearly three-fourths of the general population has an adequate preventive practice level toward COVID-19. Thus, the global, regional, national, and local governments need to establish policies and strategies to address the identified factors.